Development of Augmented Reality-Based Learning Media to Enhance Students' Understanding of Diversity Values in Civic Education - Hisam, Anugerah; Herpratiwi,; Fitri, Dina Martha (Jurnal Paedagogy, 2026)
This study aims to develop an Augmented Reality (AR)-based learning media for Civic Education and evaluate its effectiveness in improving seventh-grade students’ understanding of diversity within the context of Bhinneka Tunggal Ika (Unity in Diversity). The study employed a Research and Development (R&D) approach based on the Borg and Gall model, implemented up to the seventh stage (Operational Product Revision). Data were collected through learning achievement tests, questionnaires, and classroom observations. Qualitative data were analyzed descriptively, while quantitative data were analyzed using descriptive statistics, validity and reliability testing, a paired-samples t-test, and normalized gain (N-gain) analysis. The findings indicate that the development of the AR-based learning media was motivated by the abstract nature of diversity-related learning, which resulted in approximately 70% of students failing to achieve the minimum learning mastery standard. The developed media incorporates marker-based AR features, three-dimensional (3D) representations of Indonesia’s cultural diversity, interactive quizzes, and a glossary. The effectiveness evaluation demonstrated a substantial improvement in students’ learning achievement, with the mean score increasing from 35.19 on the pretest to 94.21 on the posttest. The paired-samples t-test further confirmed that the improvement was statistically significant (p < 0.001). In addition, students rated the media positively, with an overall acceptance score of 70.5%, indicating good usability and attractiveness. These findings suggest that the AR-based learning media is valid, practical, and effective in enhancing students’ understanding of diversity while supporting Civic Education learning grounded in the values of Bhinneka Tunggal Ika.